Impact Of Arbuscular Mycorrhizae And Gogo Rice Interaction Against Rice Blas Disease (Prycularia oryzae): - Asmiaty Sahur Sahur; Muhammad Junaid (Asosiasi Mikoriza Indonesia, 2022)
Gogo rice productivity is lower than lowland rice because one of the factors of the production gap is the control of plant-disturbing organisms. One of the diseases that attack rice plants is Blast disease, it is necessary to control efforts by utilizing micro organisms such as mycorrhizae vesicular-arbuscular (MVA). The purpose is to study the role of MVA on the growth and development of three gogo rice varieties and the level of infection intensity of blast disease (Pyricularia oryzae CAF). This research used a Randomized Block Design with the treatments were No MVA with Varieties IR-64, MVA Inoculation with Varieties IR-64, No MVA with Membrano, MVA Inoculation with Membranos, No MVA with Pelita I-1, Inoculation of MVA with Varieties of lamp I-1. The mycorrhizae treatment increased the uptake of P nutrients which was seen in plant height, dry weight yield, percentage of root associations and speed of flower formation. The mycorrhizae treatment showed a relatively low intensity of blast disease. In relation to plant resistance, mycorrhizae can suppress pathogens that cause Pyricularia oryzae CAF so that these plants have low disease intensity. Conclusion: Mycorrhizae increased the plant height, trunk and time of flower formation and P nutrient uptake, an average of 0.26 percent in leaf tissue. Mycorrhizae increased the resistance of gogo rice plants from Pyricularia oryzae CAF attack. The membramo variety showed the best growth and yields.